Update on COVID-19 vaccines and news on face masks: Vish Nene and Dieter Schillinger - Nene, Vishvanath M.; Schillinger, Dieter (International Livestock Research Institute, 2021)
Vish Nene, co-leader of the ILRI Animal and Human Health Program, and Dieter Schillinger, ILRI deputy director general of research and development–Biosciences, give updates on vaccines for COVID-19 and the use of face masks. This film was recorded on 29 January 2021. Find ILRI expertise and resources on zoonoses: ilri.org/zoonoses